Quantitative Proteomics Reveals Common and Specific Responses of a Marine Diatom Thalassiosira pseudonana to Different Macronutrient Deficiencies - Chen, Xiao-Huang; Li, Yuan-Yuan; Zhang, Hao; Liu, Jiu-Ling; Xie, Zhang-Xian; Lin, Lin; Wang, Da-Zhi (Frontiers in Microbiology, 2018)
Macronutrients such as nitrogen (N), phosphorus (P) and silicon (Si) are essential for the productivity and distribution of diatoms in the ocean. Responses of diatoms to a particular macronutrient deficiency have been investigated, however, we know little about their common or specific responses to different macronutrients. Here, we investigated the physiology and quantitative proteomics of a diatom Thalassiosira pseudonana grown in nutrient-replete, N-, P- and Si-deficient conditions. Cell growth was ceased in all macronutrient deficient conditions while cell volume and cellular C content under P- and Si-deficiencies increased. Contents of chlorophyll a, protein and cellular N decreased in both N- and P-deficient cells but chlorophyll a and cellular N increased in the Si-deficient cells. Cellular P content increased under N- and Si-deficiencies. Proteins involved in carbon fixation and photorespiration were down-regulated under all macronutrient deficiencies while neutral lipid synthesis and carbohydrate accumulation were enhanced. Photosynthesis, chlorophyll biosynthesis, and protein biosynthesis were down-regulated in both N- and P-deficient cells, while Si transporters, light-harvesting complex proteins, chloroplastic ATP synthase, plastid transcription and protein synthesis were up-regulated in the Si-deficient cells. Our results provided insights into the common and specific responses of T. pseudonana to different macronutrient deficiencies and identified specific proteins potentially indicating a particular macronutrient deficiency.